Inoculation Site from a Cutaneous Melanoma Patient Treated with an Allogeneic Therapeutic Vaccine: A Case Report - Aris, Mariana; Bravo, Alicia Inés; Barrio, María Marcela; Mordoh, José (Frontiers in Immunology, 2015)
We have developed a therapeutic vaccine consisting of a mixture of lethally-irradiated allogeneic cutaneous melanoma cell lines with BCG and GM-CSF as adjuvants. The CSF-470 vaccine is currently being assayed in a Phase II–III trial against medium-dose IFN-α2b. All vaccinated patients immunized intradermally developed large edematous erythema reactions, which then transformed into subcutaneous nodules active for several months. However, vaccine injection sites were not routinely biopsied. We describe the case of a female patient, previously classified as stage III, but who, due to the simultaneous discovery of bone metastases only received one vaccination was withdrawn from the study, and continued her treatment elsewhere. This patient developed a post-vaccination nodule which was surgically removed 7 weeks later, and allowed to analyze the reactivity and immune profiling of the inoculation site. An inflammatory reaction with zones of fibrosis, high irrigation, and brisk lymphoid infiltration, primarily composed of CD8+ and CD20+ lymphocytes, was observed. There were no remaining BCG bacilli, and scarce CD4+ and Foxp3+ T cells were determined. MART-1 Ag was found throughout the vaccination site. CD11c+ Ag presenting cells were either dispersed or forming dense nests. Some CD11c+ cells proliferated; most of them contained intracellular MART-1 Ag, and some interacted with CD8+ lymphocytes. These observations suggest a potent, long-lasting local inflammatory response with recruitment of Ag-presenting cells that incorporate melanoma Ags, probably leading to Ag presentation to naïve T cells.